Broadband and high resolution measurements of cavity loss and dispersion - Charczun, Dominik Andrzej; Kowzan, Grzegorz; Cygan, Agata; Trawiński, Ryszard S.; Lisak, Daniel; Masłowski, Piotr (Photonics Letters of Poland, 2018)
We present a method for broadband measurements of dispersion and loss of an optical cavity. We employ an optical frequency comb directly coupled into a cavity to scan the cavity modes and retrieve their shapes and positions. The measurement data is acquired using instrumental-line-shape-free Fourier transform spectrometry. This method can be developed into a powerful tool for optical loss and dispersion measurements for broadband characterization of optical elements as well as absorption and dispersion spectroscopy. Full Text: PDF References Th. Udem, R. Holzwarth, T.W. Hänsch, "Optical Frequency Metrology", Nature 416, 233–237 (2002). CrossRef R.A. McCracken, J.M. Charsley, D.T. Reid "A decade of astrocombs: recent advances in frequency combs for astronomy", Optics Express 25, 13, 15058-15078 (2017). CrossRef M.J. Thorpe, D. Balslev-Clausen, M.S. Kirchner, J. Ye, "Cavity-enhanced optical frequency comb spectroscopy: application to human breath analysis", Optics Express 16, 4, 2387-2397 (2008). CrossRef J. Domysławska et al., "Cavity ring-down spectroscopy of the oxygen B-band with absolute frequency reference to the optical frequency comb", The Journal of Chemical Physics 136, 024201 (2012). CrossRef P. Masłowski K.C. Cossel, A. Foltynowicz, J. Ye., "Cavity-Enhanced Direct Frequency Comb Spectroscopy", in G. Gagliardi and H.-P. Loock, "Cavity-Enhanced Spectroscopy and Sensing", Springer (2014). CrossRef L. Rutkowski et al., "Sensitive and broadband measurement of dispersion in a cavity using a Fourier transform spectrometer with kHz resolution", Optics Express Vol. 25, Issue 18, pp. 21711-21718 (2017). CrossRef E.D. Black, "An introduction to Pound-Drever-Hall laser frequency stabilization", American Journal of Physics 69, 79 (2001) CrossRef A. Cygan et al., "One-dimensional frequency-based spectroscopy", Optics Express. 23, 14472. 10.1364 ( 2015). CrossRef P. Masłowski et al., "Surpassing the path-limited resolution of Fourier-transform spectrometry with frequency combs", Phys. Rev. A 93, 021802(R) (2016). CrossRef L. Rutkowski, P. Masłowski, A.C. Johansson, A. Khodabakhsh, A. Foltynowicz, "Optical frequency comb Fourier transform spectroscopy with sub-nominal resolution and precision beyond the Voigt profile", Jour. of Quant. Spect. and Rad. Trans., 204, 63-73 (2018). CrossRef S. Schiller, "Spectrometry with frequency combs," Opt. Lett. 27, 766-768 (2002). CrossRef A. Cygan et al., "Absolute molecular transitions frequencies measured by three cavity-enhanced spectroscopy techniques" J. Chem. Phys. 144 214202-1-214202-11 (2016). CrossRef I.E. Gordon et al., "The HITRAN2016 Molecular Spectroscopic Database", J. Quant. Spect. Radiat. Trans. (2017). CrossRef